Limbic and cortical information processing in the nucleus accumbens - Goto, Yukiori (2008)
The nucleus accumbens regulates goal-directed behaviors by integrating information from limbic structures and the prefrontal cortex. Here, we review recent studies in an attempt to provide an integrated view of the control of information processing in the nucleus accumbens in terms of the regulation of goal-directed behaviors and how disruption of these functions might underlie the pathological states in drug addiction and other psychiatric disorders. We propose a model that could account for the results of several studies investigating limbic-system interactions in the nucleus accumbens and their modulation by dopamine and provide testable hypotheses for how these might relate to the pathophysiology of major psychiatric disorders.